The Revised EBA-Lite Methodology. (Policy Papers; Policy Paper, 2019)
The Methodology review identified three broad areas for improving the EBA-Lite methodology: (1) expanding the fundamentals and policy determinants in the CA and REER regressions to better capture the external balance of EBA-Lite countries; (2) identifying alternatives to regression models for external assessments of large exporters of exhaustible commodities; and (3) a revised approach for the assessment of external sustainability in highly indebted economies. Accordingly, the revised methodology consists of three modules: 1) Regression Module 2) Module for External Assessments of Exporters of Exhaustible Commodities 3) Module for the Assessment of External Sustainability.